Competition law in Malaysia and United Kingdom: a comparative study / Majdah Mohd Yusof, Norarifa A. Rahman and Shazwina Ahmad Mazli - Mohd Yusof, Majdah; A. Rahman, Norarifa; Ahmad Mazli, Shazwina (2012)
This research paper is a comparative study between the United Kingdom and Malaysia on the application of the Competition Act in respective countries. The main objective is to critically examine the Competition Act 2010 in Malaysia in order to promote a competitive market environment in Malaysia. It looks at how the Act is implemented in the respective countries. Furthermore, the comparison between the competition law in Malaysia with United Kingdom's competition law will be studied. From the legal point of view, the legal background of each country will be studied and whether the implementation of the Act is effective. Interviews will be conducted from the academic and student's perspective as to the justification of implementing the Act. The effectiveness of the implementation of competition law in respective countries will be inferred and suggestions or recommendations necessary for the government to improve the Competition Act in Malaysia will be made.